Characteristics of the integration sites and module structures of the Tn916 and its family - Lei Song; Jingxiu Duan; Tianren Liu; Jiaojiao Sun; Zhiling Hao (Scientific Reports)
Abstract Tn916, the most typical conjugative transposon that contains the tetM resistance gene, has been identified in various genomes. This study examined the recognized Tn916 (with an identity of > 90%) and Tn916 other family members (with identities between 60 and 90%) in all currently known complete genome and chromosome sequences, naming them Tn916.1 to Tn916.9. Tn916 and other members of this family have similar structures: AT-rich inverted repeats (IRs), with the boundaries being AT-rich stem‒loop structures; the coupling sequences in the middle, often 5 bp AT-rich regions, with the conserved base is the first base A or the last base T; the stem sequence from the host, which often matches or complements part of the IR (4–5 bp). Most Tn916 family members have ABC transporter gene clusters as resistance markers, and Tn916.9 has vancomycin resistance genes. Tn916 and other members of this family are more frequently integrated into genomes that have low GC% values. Our study elucidates the structural characteristics of the regions flanking Tn916 and other members of this family, laying a molecular foundation for further determining their deletion and integration mechanisms and aiding in controlling the spread of such antibiotic resistance in these conjugative transposons.